Partial correctness and continuous integration in computer supported education - Fonte, Daniela (2014)
In this paper we support the idea that students and teachers will benefit from a computer-based system that assesses programming exercises and provide immediate and detailed feedback: students would be able to evolve in the right direction and teachers would follow and assess more fairly their students. This assessment should outperform the typical right/wrong evaluation returned by existing tools, allowing for a flexible partial evaluation. Moreover, we adopt a concept from Agile Development, the Continuous Integration (CI), to improve students’ effectiveness. The applicability of CI reflects a better monitoring by the teams and their individual members, also providing the ability to improve the speed of the development. Besides the description of the capabilities that we require from an Automatic Grading System (AGS), we discuss iQuimera, an improved AGS that we are working on, that implements our teaching/learning principles.